Assessing the Sustainability of Broiler Waste Management Strategies in Thailand through Analytical Hierarchy Process Analysis - Bandara, Senaka; Chaichana, Chatchawan; Borirak, Nitthinan (Food, Agriculture and Natural Resources - NETWORKS, 2024)
This study addresses the imperative of sustainable broiler waste management in Thailand, a significant global producer and exporter of broiler meat. Utilizing an Analytic Hierarchy Process (AHP) analysis, it systematically evaluates three waste management strategies – direct land application, composting, and gasification – across environmental, economic, technical, and social criteria with 15 sub-criteria. Climate change is identified as the top priority sub-criterion, followed closely by water use. Gasification emerges as the most preferred option with 52.6% preference, outperforming composting (24.8%) and direct land application (22.6%). A comprehensive analysis reveals gasification's superior environmental and social performance, while direct land application demonstrates economic efficacy. Composting exhibits a well-rounded performance across all criteria. Pioneering the AHP model in broiler waste management, this study offers policymakers crucial insights for formulating sustainable long-term policies to address this pressing issue.